2006
DOI: 10.1038/nn1668
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation delays the positive effects of running on adult neurogenesis

Abstract: Social isolation can exacerbate the negative consequences of stress and increase the risk of developing psychopathology. However, the influence of living alone on experiences generally considered to be beneficial to the brain, such as physical exercise, remains unknown. We report here that individual housing precludes the positive influence of short-term running on adult neurogenesis in the hippocampus of rats and, in the presence of additional stress, suppresses the generation of new neurons. Individual housi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
351
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 410 publications
(385 citation statements)
references
References 48 publications
(36 reference statements)
23
351
9
Order By: Relevance
“…Previous studies on the effects of chronic stress on hippocampal neurogenesis demonstrated decreased cell proliferation in the dentate gyrus following chronic isolation (Dong et al, 2004), as well as several other chronic stressors (Simon et al, 2005; Lee et al, 2006;. Chronic social isolation also exacerbated the effect of another chronic stressor (daily foot-shock for 3 weeks) on the production of new hippocampal neurons (Westenbroek et al, 2004), and precluded the positive influence of short-term running on neurogenesis (Stranahan et al, 2006). Our findings are consistent with these reports, demonstrating that chronic isolation decreased the production of new neurons, which has been implicated in some hippocampal-dependent learning and memory tasks (Shors et al, 2001;Shors, 2004;Saxe et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies on the effects of chronic stress on hippocampal neurogenesis demonstrated decreased cell proliferation in the dentate gyrus following chronic isolation (Dong et al, 2004), as well as several other chronic stressors (Simon et al, 2005; Lee et al, 2006;. Chronic social isolation also exacerbated the effect of another chronic stressor (daily foot-shock for 3 weeks) on the production of new hippocampal neurons (Westenbroek et al, 2004), and precluded the positive influence of short-term running on neurogenesis (Stranahan et al, 2006). Our findings are consistent with these reports, demonstrating that chronic isolation decreased the production of new neurons, which has been implicated in some hippocampal-dependent learning and memory tasks (Shors et al, 2001;Shors, 2004;Saxe et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, exposure to acute psychological stressors, such as short-term (3-5 h) isolation, increased hippocampal IL-1 levels and produced memory impairments that were completely blocked by an intrahippocampal injection of IL-1ra (Barrientos et al, 2003(Barrientos et al, , 2004. Stressful conditions, such as social isolation, also influence several aspects of neural plasticity, including hippocampal neurogenesis (Dong et al, 2004;Westenbroek et al, 2004;Stranahan et al, 2006), which is critically important for some hippocampal-dependent learning and memory tasks (Shors et al, 2001(Shors et al, , 2002Saxe et al, 2006;Winocur et al, 2006). We have recently demonstrated that chronic mild stress, as well as chronic administration of IL-1b, markedly reduces hippocampal neurogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…Immunolabeling for BrdU and Ki67 was carried out as described 15 . Full description of the methods for brightfield and fluorescence tissue labeling are available in Supplementary Methods.…”
Section: Immunohistochemistry and Microscopymentioning
confidence: 99%
“…Full description of the methods for brightfield and fluorescence tissue labeling are available in Supplementary Methods. We quantified single-and double-labeled cells using standard protocols 15 . Detailed cell counting criteria are available in Supplementary Methods.…”
Section: Immunohistochemistry and Microscopymentioning
confidence: 99%
See 1 more Smart Citation